ENETS standardized (synoptic) reporting for endoscopy in neuroendocrine tumors. (1st March 2022) - Borbath, Ivan; Pape, Ulrich‐Frank; Deprez, Pierre H.; Bartsch, Detlef Klaus; Caplin, Martyn; Falconi, Massimo; Garcia‐Carbonero, Rocio; Grozinsky‐Glasberg, Simona; Jensen, Robert T.; Arnold, Rudolf; Ruszniewski, Philippe; Toumpanakis, C.; et al.
Abstract: Despite efforts from various endoscopy societies, reporting in the field of endoscopy remains extremely heterogeneous. Harmonisation of clinical practice in endoscopy has been highlighted by application of many clinical practice guidelines and standards pertaining to the endoscopic procedures and reporting are underlined. The aim of the proposed "standardised reporting" is to (1) facilitate recognition of gastrointestinal neuroendocrine neoplasms (NEN) on initial endoscopy, (2) to enable interdisciplinary decision making for treatment by a multidisciplinary team, (3) to provide a basis for a standardised endoscopic follow‐up which allows detection of recurrence or progression reliably, (4) to make endoscopic reports on NEN comparable between different units, and (5) to allow research collaboration between NEN centres in terms of consistency of their endoscopic data. The ultimate goal is to improve disease management, patient outcome and reduce the diagnostic burden on the side of the patient by ensuring the highest possible diagnostic accuracy and validity of endoscopic exams and possibly interventions. Abstract : Reporting in the field of endoscopy remains extremely heterogeneous. The aim of the proposed "standardised reporting" is to (1) facilitate recognition of gastrointestinal Neuroendocrine Neoplasms (NEN) on initial endoscopy, (2) to enable interdisciplinary decision making for treatment by a multi‐disciplinary team, (3) to provide a basis for a standardised endoscopic follow‐up which allows detection of recurrence or progression reliably, (4) to make endoscopic reports on NEN comparable between different units, and (5) to allow research collaboration between NEN centres in terms of consistency of their endoscopic data.